Revision of the genus Ennada Blanchard (Lepidoptera: Geometridae) - Parra, Luis E.; Alvear, Carla A. (Zootaxa, 2009)
The genus Ennada Blanchard, 1852 is reviewed and redefined. A coniform signum in the genitalia of the female and androconium in the basal third of the costa of the valvae in the male genitalia constitute diagnostic characters for the genus. The genera Phyllia Blanchard 1852 and Anchiphyllia Butler 1893 are junior synonyms of Ennada. The following species are included: E. flavaria Blanchard 1852, E. pellicata (Felder & Rogenhofer 1875) comb. nov., and E. blanchardi sp. nov. The geographic distribution of the genus is between 29º and 44º S in Chile. The adults, their genitalia and distribution are described and illustrated. A key to differentiate the species is provided.